PENGARUH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 60/PUU-XXII/2024 TERHADAP KEKHUSUSAN PARTAI POLITIK LOKAL ACEH DALAM PILKADA 2024 - Munandar, Agung; Zulfikar, Muhammad Nahyan; Darusman, Chandra; Maulana, Jefrie (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
Law No. 11/2006 on the Governance of Aceh (UUPA) addresses only the nomination thresholds for local political parties. However, Qanun Aceh No. 12/2016 has standardized the nomination threshold for regional heads from national political parties to 15%, which conflicts with Indonesian Law No. 10/2016. The Constitutional Court Decision No. 60/PUU-XXII/2024, which reduced the threshold percentage, has resulted in a loss of specificity for local political parties in Aceh. This research aims to analyze the impact of the Constitutional Court Decision on local elections in Aceh, address the normative conflicts between local and higher regulations, elucidate the hierarchy of legislation, and propose solutions. The research employs a normative juridical method, using secondary data obtained from literature. Findings indicate that the regulation of national political parties should be governed by national laws and their derivative regulations to avoid normative conflicts, while the regulation of local political parties can be managed through regional regulations such as qanun. To resolve normative conflicts, preventive measures include harmonizing laws and regulations, while repressive measures involve either the annulment of qanun by the government or material testing by the Supreme Court and Constitutional Court concerning UUPA (Aceh Special Autonomy Law).